Fractography and Microstructural Analysis of As-Built and Stress Relieved DMLS Ti6Al4V (ELI) Plates Subjected to High Velocity Impact - Teboho C. Moleko; Maina Maringa; Willie B. Du Preez (Advances in Materials Science and Engineering)
This paper presents fractographic and microstructural analysis of as-built and stress relieved DMLS Ti6Al4V (ELI) plates with thicknesses of 8 mm, 10 mm, 12 mm, and 14 mm, impacted by high velocity projectiles. Fractography was performed through scanning electron microscopy on the surfaces of the projectile holes, while microstructural analysis of specimens extracted from the plates close to and far from the projectile holes was conducted by way of optical microscopy. Fractography revealed brittle behavior at the entry points of the penetration holes and ductile behavior at the exit points of the penetration holes. Microstructural analysis revealed microstructural changes in the alloy and a gradual increase of the β-phase fraction toward the edge of the projectile holes through all the plate thicknesses.